Viroids: From Genotype to Phenotype Just Relying on RNA Sequence and Structural Motifs - Flores, Ricardo; Serra, Pedro; Minoia, Sofia; Di Serio, Francesco; Navarro, Beatriz (Frontiers in Microbiology, 2012)
As a consequence of two unique physical properties, small size and circularity, viroid RNAs do not code for proteins and thus depend on RNA sequence/structural motifs for interacting with host proteins that mediate their invasion, replication, spread, and circumvention of defensive barriers. Viroid genomes fold up on themselves adopting collapsed secondary structures wherein stretches of nucleotides stabilized by Watson-Crick pairs are flanked by apparently unstructured loops. However, compelling data show that they are instead stabilized by alternative non-canonical pairs and that specific loops in the rod-like secondary structure, characteristic of Potato spindle tuber viroid and most other members of the family Pospiviroidae, are critical for replication and systemic trafficking. In contrast, rather than folding into a rod-like secondary structure, most members of the family Avsunvioidae adopt multibranched conformations occasionally stabilized by kissing loop interactions critical for viroid viability in vivo. Besides these most stable secondary structures, viroid RNAs alternatively adopt during replication transient metastable conformations containing elements of local higher-order structure, prominent among which are the hammerhead ribozymes catalyzing a key replicative step in the family Avsunvioidae, and certain conserved hairpins that also mediate replication steps in the family Pospiviroidae. Therefore, different RNA structures ⎯either global or local ⎯ determine different functions, thus highlighting the need for in-depth structural studies on viroid RNAs.